Pengaruh Citra Merek dan Kepercayaan terhadap Keputusan Pembelian Iphone di Erafone Kota Bekasi - Akbar, Muhamad; Nadia, Naila Vira (BISMA : Business and Management Journal, 2024)
This research aimed to find out and analyze how big the influence of brand image and brand trust on iPhone purchasing decisions in Erafone Bekasi City. The research method used was a quantitative method with the research sample taken was 100 people. The data processing technique used is the multiple linear regression method. The research results showed that there was a partially significant influence between brand image on purchasing decisions where t-count is 8.913 > t-table 1.984 and with a significance value of 0.000 < 0.05. There was a partially significant influence between brand trust on purchasing decisions where t-count was 7.134 > t-table 1.984 and with a significance value of 0.000 < 0.05. There was a significant influence simultaneously between brand image and brand trust on purchasing decisions as shown by f-count 399.050 > f-table 3.09. The contribution made by brand image and brand trust simultaneously on purchasing decisions was 88.9%, while the remaining 11.1% was influenced by other factors not included in this research